2015
DOI: 10.1371/journal.pone.0141212
|View full text |Cite
|
Sign up to set email alerts
|

Stop and Go – Waves of Tarsier Dispersal Mirror the Genesis of Sulawesi Island

Abstract: The Indonesian island of Sulawesi harbors a highly endemic and diverse fauna sparking fascination since long before Wallace’s contemplation of biogeographical patterns in the region. Allopatric diversification driven by geological or climatic processes has been identified as the main mechanism shaping present faunal distribution on the island. There is both consensus and conflict among range patterns of terrestrial species pointing to the different effects of vicariant events on once co-distributed taxa. Tarsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 58 publications
(104 reference statements)
5
58
0
Order By: Relevance
“…Populations of Babirusa and SWP in these zones of endemism were also strongly morphologically differentiated ( Figure 2). Altogether, these data and analyses indicate that, despite some differences, the zones of endemism identified in tarsiers, macaques, toads and lizards [18,[40][41][42][43][44][45]47] are largely consistent with the population structure and morphological differentiation in the three species studied here. This is particularly striking for the north arm of Sulawesi (NW, NC, and NE in Figure 4), where we identify two highly differentiated populations (reflected in both mtDNA and nuclear data sets) in all three taxa.…”
Section: Supplementary Materialssupporting
confidence: 75%
See 1 more Smart Citation
“…Populations of Babirusa and SWP in these zones of endemism were also strongly morphologically differentiated ( Figure 2). Altogether, these data and analyses indicate that, despite some differences, the zones of endemism identified in tarsiers, macaques, toads and lizards [18,[40][41][42][43][44][45]47] are largely consistent with the population structure and morphological differentiation in the three species studied here. This is particularly striking for the north arm of Sulawesi (NW, NC, and NE in Figure 4), where we identify two highly differentiated populations (reflected in both mtDNA and nuclear data sets) in all three taxa.…”
Section: Supplementary Materialssupporting
confidence: 75%
“…Previous studies have identified endemic zones that are common to macaques, toads [18,40], tarsiers [41][42][43][44] and lizards [45]. We tested whether the same area of endemism are linked to the population structure in our three species by generating a phylogenetic tree for each species using mtDNA and defined 5-6 haplogroups per species based on well-supported clades (Figure 4a-c; Figure S4-6).…”
Section: Geological History Of Past Land Isolation Correlates With Zomentioning
confidence: 99%
“…Sea level changes in the Pliocene that periodically exposed and obliterated land bridges shaped dispersal and diversification of Sulawesi tarsiers (Driller et al 2015), and later, responding to the immense sea level fluctuations caused by Pleistocene glacial cycles, also macaques. In fact, changes in sea level and associated shifts in the size and connections of landmasses are implicated in the dispersal and subsequent evolution of several groups of primates.…”
Section: Sea Level Changementioning
confidence: 99%
“…Molecular analysis suggests that the main tarsier lineages diversified in the Miocene, but DNA data alongside acoustic evidence have revealed the complexities of their subsequent evolution in the Pliocene. For the Sulawesi clade, this included dispersal across the region, with range expansions and consequent late Pliocene diversification being linked to periodic exposure, due to sea level change, of shelves and land-bridges, as well as lineage divergence promoted by Pliocene tectonic faulting and the associated emergence of lakes (Driller et al 2015).…”
Section: Tarsiersmentioning
confidence: 99%